2013
DOI: 10.1103/physrevb.87.125116
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the electronic band gap in lanthanide oxides

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
138
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 39 publications
20
138
0
Order By: Relevance
“…Most notably, Rödl et al 20 showed that the screened hy-brid functional HSE03, which they used as input for their G 0 W 0 calculations, yields good band gaps on its own. We recently reported that the screened hybrid functional 'screened-exchange LDA' (sX-LDA) successfully reproduces the electronic properties of CeO 2 , as well as those of lanthanide (X=La,Ce,...,Lu) 29 and transition metal (X=Ti, Cr, Fe) 38 sesquioxides X 2 O 3 . Interestingly, we observed that variations in treatment of the screened exchange interaction in the hybrid functional approach can lead to qualitative differences of the predicted properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, Rödl et al 20 showed that the screened hy-brid functional HSE03, which they used as input for their G 0 W 0 calculations, yields good band gaps on its own. We recently reported that the screened hybrid functional 'screened-exchange LDA' (sX-LDA) successfully reproduces the electronic properties of CeO 2 , as well as those of lanthanide (X=La,Ce,...,Lu) 29 and transition metal (X=Ti, Cr, Fe) 38 sesquioxides X 2 O 3 . Interestingly, we observed that variations in treatment of the screened exchange interaction in the hybrid functional approach can lead to qualitative differences of the predicted properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid functionals have been shown to be versatile methods for the study of correlated materials, often on par with quasiparticle methods [27][28][29] , while generally performing great for sp semiconductors and materials of practical interest, such as GaN or ZnO 27 . A number of hybrid functional studies on late transition metal oxides has been reported 17,20,[30][31][32][33][34][35][36][37][38] , with band gaps varying with the fraction of included Hartree-Fock exchange.…”
Section: Introductionmentioning
confidence: 99%
“…15,18,[31][32][33][34][35][36] Extended solids including CeO2 have also served as important test cases for evaluating whether accurate theoretical methodology can treat the 4f-electrons simply as part of the core, or whether a more demanding approach should be followed that allows the 4f-electrons to delocalize and participate in bonding. [37][38][39][40][41][42][43][44][45][46] Cerium intermetallics have been at the forefront of condensed matter physics and development of the Anderson impurity model for heavy fermion systems and Kondo insulators. 47 For example, Ce L3-and M5,4-edge XANES spectroscopic investigations of CeRu3, CeRh3, and CePt3 have provided evidence for 4f-electron delocalization, 20,23,[48][49] and L3-edge investigations of intermetallics such as CeCoIn5 have led to new understanding of their remarkable magnetic and superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid functionals have been used to calculate the single particle band structures of various transition metal oxides. [50][51][52][53][54] The HSE functional was used previously to study the MIT in VO 2 with changing the crystal structure, 50 but based on experimental atomic coordinates. Here, we find that the sX functional will reproduce the correct single-particle electronic structure in all the three phases of V 2 O 3 without any fitting parameter.…”
Section: Introductionmentioning
confidence: 99%